Implementation of a residency program in anesthesiology in the Northeast of Brazil: impact on work processes and professional motivation - Fernandes,Cláudia Regina (2015)
BACKGROUND AND OBJECTIVES: To understand, through the theory of social representations, the influence exerted by the establishment of a residency program in anesthesiology on anesthetic care and professional motivation in a tertiary teaching hospital in the Northeast of Brazil. METHOD: Qualitative methodology. The theoretical framework comprised the phenomenology and the social representation theory. Five multidisciplinary focus groups were formed with 17 health professionals (five surgeons, five anesthesiologists, two nurses, and five nursing technicians), who work in operating rooms and post-anesthesia care units, all with a prior and a posteriori experience to the establishment of residency. RESULTS: From the response content analysis, the following empirical categories emerged: motivation to upgrade, recycling of anesthesiologists and improving anesthetic practice, resident as an interdisciplinary link in perioperative care, improvements in the quality of perioperative care, and recognition of weaknesses in the perioperative process. It was evident from upper gastrointestinal bleeding secondary to prolonged intubation that the creation of a residency in anesthesiology brings advancements that are reflected in the motivation of anesthesiologists; the resident worked as an interdisciplinary link between the multidisciplinary team; there was recognition of weaknesses in the system, which were identified and actions to overcome it were proposed. CONCLUSION: The implementation of a residency program in anesthesiology at a tertiary education hospital in the Northeast of Brazil promoted scientific updates, improved the quality of care and processes of interdisciplinary care, recognized the weaknesses of the service, developed action plans and suggested that this type of initiative may be useful in remote areas of developing countries.